PS01.236: MEDIASTINOSCOPIC SALVAGE ESOPHAGECTOMY FOR RECURRENT ESOPHAGEAL CANCER AFTER DEFINITIVE CHEMORADIOTHERAPY IN A PREVIOUSLY PNEUMONECTOMIZED PATIENT. (14th September 2018) - Okumura, Tomoyuki; Seto, Yasuyuki; Aikou, Susumu; Moriyama, Makoto; Sekine, Shinich; Hojo, Shozo; Arai, Mie; Baba, Hayato; Hirano, Katsuhisa; Shibuya, Kazuto; Hashimoto, Isaya; Yoshioka, Isaku; et al.
Abstract: Background: Mediastinoscopic esophagectomy is a minimally invasive surgery for thoracic esophageal cancer avoiding one-lung ventilation or transthoracic procedure. Methods: We performed for the first time in the literature, salvage esophagectomy with combination of mediastinoscopic cervical approach and laparoscopic/mediastinoscopic transhiatal approach for recurrent thoracic esophageal squamous cell carcinoma (ESCC) after definitive chemoradiotherapy (dCRT) in a patient who had previously undergone a left pneumonectomy for primary lung cancer. Results: A 66-year-old man was diagnosed as local recurrence of lower ESCC (cT3N0M0 cStage II) at 9 years after dCRT. His medical history included left-sided pneumonectomy for lung adenocarcinoma 9 years previously. Then the patient was diagnosed as lower thoracic ESCC (cT3N1M0 cStage III) at 2 months after pneumonectomy. He received dCRT consisting of CDDP/5-FU infusion and irradiation (60 Gy) and achieved complete response. No evidence of tumor recurrence was observed at endoscopic surveillance up until 6 years after dCRT. For this present surgery, a cervical wound was made and the intramediastinal procedure was performed under pneumomediastinum. After mobilization of upper/middle thoracic esophagus, the esophageal wall was safely separated from the remaining part and the stump of the left main bronchus. Dense adhesions between the esophagus and fibrotic tissue at the site of previous left mediastinal pleural resection was divided using a sealing device. In the abdomen, 5 ports were inserted to perform abdominal and transhiatal procedures under CO2 insufflation. After mobilization of the stomach, fibrotic scar tissue around the lower esophagus was divided using a sealing device and the peri-esophageal space dissected from cervical and transhiatal approach were connected to completely mobilize the thoracic esophagus. The esophagectomy was uneventfully carried out followed by reconstruction with gastric conduit via retrosternal rout. Pathological findings demonstrated a moderately differentiated ESCC (pT3-AD pN1 M0 pStage III), indicating that R0 resection was successfully performed. The patient has been closely observed as an outpatient and was alive and healthy at 3 months after the operation without tumor recurrence. Conclusion: Mediastinoscopic esophagectomy is a safe and curative treatment strategy for esophageal cancer patients who had a previous pneumonectomy, even in salvage surgery for recurrent cancer after dCRT. Disclosure: All authors have declared no conflicts of interest.